On “Westsplaining,” realism, and technologies of the Self. : A Foucauldian reading of the realist commentary on Ukraine - Kazharski, Aliaksei (Journal of Regional Security, 2024)
The article offers a Foucauldian reading of the Western realist commentary on the Russo-Ukrainian war which often faces the charges of “Westsplaining.” It situates this commentary in the broader context of knowledge production and the power-knowledge nexūs it reproduces and conceptualizes realism as a discourse in the Foucauldian sense. As the article argues, this conceptualization allows one to capture its specific technologies of power which, in this case, can be understood as a form of technology of the Self, or, in other words, the disciplining of the collective subjects of world politics (nation-states) through the specifically realist constructs of rationality and prudence that all states are expected to adhere to in the making of their foreign policy. Additionally, the article suggests that this conceptualization of realism as a discourse can be analytically helpful in making sense of the way in which very different genres such as academic research and the op-ed policy commentary, frequently provided by realist IR scholars, are connected through the political economy of knowledge production, thus forming a relationship of discursive symbiosis and mutual legitimation.